Sustainable Aluminum Recycling Method - Haikal, Khaireez; Yusuf, Nur Kamilah; Ariffin Hamdan; Emieza Nasha (Journal of Multi-Disciplinary Engineering Reviews, 2024)
Aluminium, renowned for its advantageous combination of low weight and high strength, has firmly established itself as a fundamental component of contemporary industrial sectors, leaving a lasting impact on diverse fields such as aerospace engineering and ordinary consumer goods. However, the widespread use of this adaptable metallic element results in the production of significant quantities of waste and discarded materials, hence requiring the implementation of efficient recycling strategies. This comprehensive review study examines the range of recycling procedures commonly used in the aluminium sector, discussing their historical importance and investigating novel approaches that have the potential to transform aluminium recycling. The utilisation of traditional procedures, shown by conventional recycling practises, provides significant knowledge regarding the progression of the area. Nevertheless, the advent of solid-state recycling and direct recycling methods presents a positive outlook for the future, since it brings about increased resource efficiency, lower energy requirements, and a smaller ecological impact. This article functions as a comprehensive manual outlining several recycling procedures, providing a detailed analysis of their unique attributes, benefits, and obstacles. This assessment seeks to shed light on the progress made in aluminium recycling, to highlight sustainable practises that can alter the sector, promote energy saving, and reduce waste output. These practises are in line with the current emphasis on environmental stewardship. This review study serves as a guiding tool in our examination of aluminium recycling methodologies, providing direction toward the establishment of a sustainable aluminium sector.